Panduan lapangan primata Indonesia - Supriatna, Jatna; Wahyono, Edy Hendras (Jakarta : Yayasan Obor Indonesia, 2000)
On primates in Indonesia.
Includes bibliographical references (p. 314-330).
Keywords: Primates -- Indonesia -- Guidebooks